Roles of transcription factor eomesodermin in the trophectoderm and definitive endoderm lineages of the murine embryo - Bisia, AM (2022)
Eomesodermin (Eomes), a member of the T-box family of transcription factors, is required for the specification of a multitude of lineages during mouse gastrulation. Initially it is expressed in the trophectoderm (TE) of the pre-implantation blastocyst, where it is essential for peri-implantation development. Eomes is also expressed in the post- implantation embryo, where it has a critical role in the specification of several lineages during gastrulation, including the definitive endoderm (DE). The DE is fated to give rise to the gut tube and all gut-associated organs of the developing embryo. Although Eomes is necessary in both, the molecular mechanisms by which it acts to maintain or specify these two diverse cell lineages remain largely unknown. The aim of my thesis was to investigate how Eomes functions at a cellular level to generate these distinct lineages.